Actein alleviates 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin‐mediated cellular dysfunction in osteoblastic MC3T3‐E1 cells. Issue 12 (24th August 2017) - Choi, Eun Mi; Suh, Kwang Sik; Jung, Woon‐Won; Park, So Young; Chin, Sang Ouk; Rhee, Sang Youl; Pak, Youngmi Kim; Chon, Suk
Abstract: The environmental pollutant 2, 3, 7, 8‐tetrachlorodibenzo‐p‐dioxin (TCDD) is known to affect bone metabolism. We evaluated the protective effects of the triterpene glycoside actein from the herb black cohosh against TCDD‐induced toxicity in MC3T3‐E1 osteoblastic cells. We found that TCDD significantly reduced cell viability and increased apoptosis and autophagy in MC3T3‐E1 osteoblastic cells ( P  < .05). In addition, TCDD treatment resulted in a significant increase in intracellular calcium concentration, mitochondrial membrane potential collapse, reactive oxygen species (ROS) production, and cardiolipin peroxidation, whereas pretreatment with actein significantly mitigated these effects ( P  < .05). The effects of TCDD on extracellular signal‐related kinase (ERK), aryl hydrocarbon receptor, aryl hydrocarbon receptor repressor, and cytochrome P450 1A1 levels in MC3T3‐E1 cells were significantly inhibited by actein. The levels of superoxide dismutase, ERK1, and nuclear factor kappa B mRNA were also effectively restored by pretreatment with actein. Furthermore, actein treatment resulted in a significant increase in alkaline phosphatase (ALP) activity and collagen content, as well as in the expression of genes associated with osteoblastic differentiation (ALP, type I collagen, osteoprotegerin, bone sialoprotein, and osterix). This study demonstrates the underlying molecular mechanisms of cytoprotection exerted by actein against TCDD‐induced oxidative stress and osteoblast damage.